Manpower Planning dalam Pendidikan Islam: Integrasi Nilai Tauhid, Amanah, dan Maslahah - Sindi Saputri; Sri Wet Susanti; Asmendri Asmendri; Milya Sari (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
Human resource planning (manpower planning) in Islamic education is a strategic component that determines institutional sustainability and educational quality amid challenges of professionalism, unequal teacher distribution, and rapid digital transformation. This article aims to analyze human resource planning in Islamic education from an Islamic philosophical perspective by emphasizing ontological, epistemological, and axiological dimensions, as well as to formulate an integrative and applicable human resource planning model. This study employs a qualitative approach using a library research design, reviewing relevant national and international literature in Islamic educational management and human resource planning. The findings indicate that human resource planning in the Islamic perspective extends beyond efficiency and productivity, emphasizing spiritual and moral development through the values of tawhid, amanah (trust), adl (justice), ihsan (excellence), and maslahah (public benefit). The study also identifies structural challenges in Islamic educational institutions in Indonesia, including limited professional competence and digital literacy among educators, weak long-term planning, and unequal distribution of teachers across regions. As its main contribution, this article proposes the Islamic Tauhidi Human Resource Planning Model, a conceptual framework that integrates Islamic philosophical principles with modern strategic management practices. This model offers an alternative paradigm for managing human resources in Islamic education that is ethical, professional, adaptive to socio-technological changes, and oriented toward sustainable public benefit.